ŞEKLİ EŞİTLİK DOKTRİNİNDEN; MADDİ EŞİTLİĞİN GETİRİSİ OLAN POZİTİF AYRIMCILIĞA BİR BAKIŞ - (:unkn) unknown (My University, 2015)
Bu makalede, eşitlik anlayışında iki temel ayrım olarak olan maddi ve şekli eşitlik doktrinleri, pozitif ayrımcılık perspektifinden ele alınmıştır. Bu anlamda, pozitif ayrımcılığın ayrımcılık ifadesinin ötesinde olarak gerçek eşitliği sağlamak için bir araç olduğu ifade edilebilecektir. Öyle ki, yarışa eşit çizgide başlamayanların sonuç çizgisine adil bir şekilde ulaştıklarından da bahsedilemeyecek, ancak pozitif ayrımcılık uygulamaları ile bu hakkaniyet sağlanabilecektir.

In this article, we discuss the equality isue, whereas in some cases, in figure there ise disproportion, but in content, there is equality, and this is what we call positive discrimination. In this perspective, positive discrimination, despite the fact that we are using the word discrimination that is thereal opposite of equality, may be real equality. In fact, in some cases, when we start with real equality, we might end up with discrimination. Therefore, positive discrimination is needed in some cases in order to achieve real equality.
(THEORY OF EQUALITY IN THE FORM AND CONSEQUENCE OF EQUALITY IN CONTENT LEADING TO POSITIVE DISCRIMINATION)
Keywords: Hukuk